2011
DOI: 10.1111/j.1445-5994.2009.02134.x
|View full text |Cite
|
Sign up to set email alerts
|

Study of compliance with a clinical pathway for suspected pulmonary embolism

Abstract: Compliance with this clinical pathway allowed emergency department doctors in an Australian university teaching hospital to complete diagnostic testing for suspected pulmonary embolism appropriately unless non-emergency department doctors became involved. Compliance with this pathway altered the distribution of diagnostic tests performed with less reliance on CTPA, but was not associated with better patient outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
8
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 16 publications
3
8
0
Order By: Relevance
“…This was illustrated in a study conducted in the ED of a Sydney tertiary teaching hospital that showed suboptimal compliance with a clinical pathway that involved assessment of Wells PTP with D-dimer, V/Q scanning and CTPA, particularly when non-ED doctors became involved. 17 The overall prevalence of PE in our study was significantly lower (6.3% vs 16.9%, P < 0.005), and was similar to PE prevalence in those with a low PTP, when compared with pooled data of patients undergoing CTPA across four other studies. 10 This suggests our institution with easy access to CTPA had a much lower threshold for suspecting PE, and in many cases PE may not be a warranted inclusion in the differential diagnosis.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…This was illustrated in a study conducted in the ED of a Sydney tertiary teaching hospital that showed suboptimal compliance with a clinical pathway that involved assessment of Wells PTP with D-dimer, V/Q scanning and CTPA, particularly when non-ED doctors became involved. 17 The overall prevalence of PE in our study was significantly lower (6.3% vs 16.9%, P < 0.005), and was similar to PE prevalence in those with a low PTP, when compared with pooled data of patients undergoing CTPA across four other studies. 10 This suggests our institution with easy access to CTPA had a much lower threshold for suspecting PE, and in many cases PE may not be a warranted inclusion in the differential diagnosis.…”
Section: Discussionsupporting
confidence: 76%
“…Such algorithms have been shown to be safe and cost‐effective in clinical trial settings, but face challenges when being implemented in real‐life practice. This was illustrated in a study conducted in the ED of a Sydney tertiary teaching hospital that showed suboptimal compliance with a clinical pathway that involved assessment of Wells PTP with d ‐dimer, V/Q scanning and CTPA, particularly when non‐ED doctors became involved …”
Section: Discussionmentioning
confidence: 99%
“…A further 99 low Wells PTP subjects underwent CTPA without d ‐dimer testing; only two CTPA confirmed pulmonary emboli. This underutilisation of the d ‐dimer in those with a low PTP disregards the findings and conclusions from previous studies …”
Section: Observed and Standard Protocol Intervention Cost Analysis Fomentioning
confidence: 51%
“…Institutional implementation of a clinical algorithm utilising the Wells score and D‐dimer has been shown to reduce the number of CTPAs being performed in a Melbourne tertiary Hospital . However, compliance to such clinical algorithms is difficult to achieve in practice as demonstrated in by a retrospective audit in the ED of a Sydney tertiary teaching hospital . This may be improved in the current era of electronic medical record order sets with computerised decision support systems.…”
Section: Discussionmentioning
confidence: 99%
“…14 However, compliance to such clinical algorithms is difficult to achieve in practice as demonstrated in by a retrospective audit in the ED of a Sydney tertiary teaching hospital. 15 This may be improved in the current era of electronic medical record order sets with computerised decision support systems. Indeed, the effectiveness of this approach was shown by a higher positive yield rate of CT angiography for PE with implementation of a physician order entry-based computerised decision support system when compared to a retrospective pre-interventional comparison group.…”
Section: Discussionmentioning
confidence: 99%